1979
DOI: 10.5962/bhl.title.138449
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate animals : collection and preservation /

Abstract: Preserving Living animals should be placed first in 50 per cent alcohol and then in 70-90 per cent alcohol. Alternatively, they may be placed directly in 3-5 percent neutral formalin solution. If material is being collected for subsequent cytological examination specialist literature on fixation techniques should be consulted. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 10 publications
0
31
1
3
Order By: Relevance
“…Still, we demonstrated that methodological constraints, such as the use of formalin for preservation, can hinder abundance estimations and species identification of important meroplanktonic components, such as sponge and lecithotrophic bryozoan larvae, even though samples are collected very close to parental habitats. The implications of the use of formalin for the identification of adults and early stages of various marine animals have been reported in the literature (see Lincoln & Sheals 1979, Nishikawa & Terazaki 1996, Geldmacher & Wieland 1999 and it is also commonly accepted (although no explicit publications exist) that formalin has detrimental effects on various invertebrate larvae. However, and in spite of such knowledge, this remains a commonly-employed method for preserving invertebrate larvae and plankton in general.…”
Section: Discussionmentioning
confidence: 99%
“…Still, we demonstrated that methodological constraints, such as the use of formalin for preservation, can hinder abundance estimations and species identification of important meroplanktonic components, such as sponge and lecithotrophic bryozoan larvae, even though samples are collected very close to parental habitats. The implications of the use of formalin for the identification of adults and early stages of various marine animals have been reported in the literature (see Lincoln & Sheals 1979, Nishikawa & Terazaki 1996, Geldmacher & Wieland 1999 and it is also commonly accepted (although no explicit publications exist) that formalin has detrimental effects on various invertebrate larvae. However, and in spite of such knowledge, this remains a commonly-employed method for preserving invertebrate larvae and plankton in general.…”
Section: Discussionmentioning
confidence: 99%
“…within alcohol-filled petridishes. The ready specimens were then preserved as per Lincoln and Sheals (1979 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further description on the morphology of the sea stars and photographic records were made. All the samples were preserved in 70% ethanol (Lincoln & Sheals, 1979) and stored in References Collection Museum, Centre For Marine & Coastal Studies (CEMACS), Universiti Sains Malaysia.…”
Section: Methodsmentioning
confidence: 99%